PENGARUH PENGEMBANGAN KARIER DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PERKEBUNAN MITRA OGAN KANTOR KEBUN PIN-1 KARANG DAPO - Rr Dimas Veronica Priharti; Hesty Resy Ria (KOLEGIAL, 2023)
This research aimed to find out the influence of career development and work discipline on employees’ job satisfaction at PT. Perkebunan Mitra Ogan Kantor Kebun PIN-1 Karang Dapo. The data collection technique used in this research was through the distribution of questionnaires. The population was 129 people and the sample was 56 people. The data analysis technique used was multiple linear regression. Based on the results of partial analysis, there was an influence of career development on employees’ job satisfaction at PT. Perkebunan Mitra Ogan Kantor Kebun PIN-1 Karang Dapo with a t-count value of 4.503. The work discipline variable had an influence on employees’ job satisfaction at PT. Perkebunan Mitra Ogan Kantor Kebun PIN-1 Karang Dapo with a t-count value of 13.011. Simultaneously, there was an influence of career development and work discipline on employees’ job satisfaction at PT. Perkebunan Mitra Ogan Kantor Kebun PIN-1 Karang Dapo with a F-count value of 116.531. The coefficient of determination (R2) obtained was 0.815. This meant that the contribution of the influence of career development and work discipline on job satisfaction was 81.5%, while the remaining 18.5% was influenced by other variables not mentioned in this research such as supervision, salary, communication, working conditions, and facilities according to Gilmer (quoted in Sutrisno 2020:77).